Importance of Accounts Receivable and Accounts Payable Management (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
Accurate tracking and reporting of receivables provide valuable insights for financial planning and forecasting. It helps in predicting cash inflows, budgeting, and making informed decisions regarding investments and expenditures. Effective management of payables helps maintain a healthy working capital cycle. It ensures that the company has the necessary liquidity to meet its short-term obligations, contributing to overall financial stability and reducing the risk of insolvency. The paper discusses the essence and significance of managing receivables and payables, and presents a strategy for managing receivables and payables.